Teknik Perbanyakan Nilam dengan Kultur Jaringan - Zuyasna Zuyasna (Fakultas Pertanian, Universitas Syiah Kuala, 2009)
In Vitro Propagation of Pogostemon Cablin BenthABSTRACT. The objective of this experiment was to obtain suitable medium for rapid multiplication of Pogotemon cablin Benth using tissue culture method. The research was conducted from January to June 2008 at the Tissue Culture Lab of Fakultas Pertanian Unsyiah, Banda Aceh. Leaves, petioles, and stems of Clone Tapak Tuan was used on this experiment as explants material, and induced them in the four kinds modified MS medium. The result showed that the modified MS media M1 was the suitable media for rapid adventitious shoot multiplication of Pogostemon cablin Benth clone Tapak Tuan. Adventitious shoot be regenerated from the petiole and the stems of plantlet Pogostemon cablin Benth. The average adventitious shoots generate from petiole and stems on Media M1 were 5.33 and 6 consecutively.